THE LOGICAL-SEMANTIC STRUCTURE OF LEGISLATIVE SENTENCES - DESCHAMPS, Karen; SMESSAERT, Hans (Comparative Legilinguistics, 2009)
This article analyses the logical-semantic structure of legislative sentences from a linguistic point-of-view. First, it is examined which elements constitute the meaning of legislative sentences. The following norm elements will be discussed: legal modality, norm subject, act, conditions of application, time and space, norm authority and negation. In the second part of the article, the logical-semantic relations between these elements are analysed. Following Bowers (1989), these logical-semantic relations are represented in a predicate-argument structure on different levels.